Ethical perspectives on public top leadership of digitalization - Kristensen, Kenneth (Politica, 2023)
Digitalization of the public sector is here to stay, and it involves significant ethical dilemmas that the top management must actively address. This article offers an overview of ethical themes in digitalization and several concrete examples. The top management has the responsibility, power and opportunities, and it is therefore clear that there is no neutral position for the top management in relation to the use of digital technologies. The article argues that it is not enough for the top management to respect political priorities and involves public values among stakeholders. Based on communicative ethics, the top management must also seek insight into digitalization and formulate its own ethical stance in the digital dilemmas.